UIN Ar-Raniry Nature-Loving Students’ Reception on Ecology Verses - Athfal, Khairul (TAFSE: Journal of Qur'anic Studies, 2023)
Ecology studies the reciprocal relationship between living organisms and their environment. The Al-Quran contains numerous verses that touch upon ecological themes. The ongoing reality, however, the ecological conditions of environments have not been properly solved which is evident by the rampant illegal logging and the lack of public awareness about environmental conservation. Some efforts to overcome the problem of environmental protection have been carried out by the student’s association of PA-LH Gainpala at Ar-Raniry University in Banda Aceh. This study aims to examine how ecological verses including their meanings and implications were understood and implemented in Gainpala. The type of this study is field research, and the data were collected through interviews and documentation. Then, the data were analyzed and presented using descriptive analysis. The results of the study show that Gainpala members generally had the same understanding of environmental ecology, yet they differed in terms of its implementation in protecting environments such as maintaining cleanliness and promoting environmental campaigns. Furthermore, Gainpala members also understood the messages contained in the Al-Quran, but they had not fully grasped yet the concept of ecological environment mentioned in the Al-Quran.